# 场波知识整理——1.2赫兹天线

3 篇文章 0 订阅

{ ∇ × E ‾ = − ∂ B ‾ ∂ t ∇ × H ‾ = J ‾ + ∂ D ‾ ∂ t ∇ ⋅ D ‾ = ρ ∇ ⋅ B ‾ = 0 \left\{ \begin{aligned} &\nabla\times\overline{E}=-\frac{\partial\overline{B}}{\partial{t}} \\ &\nabla\times\overline{H}=\overline{J}+\frac{\partial\overline{D}}{\partial{t}}\\ &\nabla\cdot\overline{D}=\rho\\ &\nabla\cdot\overline{B}=0 \end{aligned} \right.

J ‾ = d P ‾ d t = z ^ d ( q l cos ⁡ ω t ) δ ( r ) d t \overline{J}=\frac{d\overline{P}}{dt}=\hat{z}\frac{d(ql\cos\omega{t})\delta{(r)}}{dt}

∇ ⋅ B ‾ = 0 \nabla\cdot\overline{B}=0

∇ × E ‾ = − ∂ ∂ t ( ∇ × A ‾ ) \nabla\times\overline{E}=-\frac{\partial}{\partial{t}}(\nabla\times\overline{A})

E ‾ = − ∂ ∂ t A ‾ − ∇ ϕ \overline{E}=-\frac{\partial}{\partial{t}}\overline{A}-\nabla\phi

∇ × H ‾ = ∂ D ‾ ∂ t + J ‾ 1 μ 0 ∇ × ∇ × A ‾ = ϵ 0 ∂ ∂ t ( − ∂ ∂ t A ‾ − ∇ ϕ ) + J ‾ ∇ ( ∇ ⋅ A ‾ ) − ∇ 2 A ‾ = μ 0 ϵ 0 ( − ∂ 2 ∂ t 2 A ‾ − ∂ ∂ t ∇ ϕ ) + μ 0 J ‾ \begin{aligned} &\nabla\times\overline{H}=\frac{\partial\overline{D}}{\partial{t}}+\overline{J}\\ &\frac{1}{\mu_0}\nabla\times\nabla\times\overline{A}=\epsilon_0\frac{\partial}{\partial{t}}(-\frac{\partial}{\partial{t}}\overline{A}-\nabla\phi)+\overline{J}\\ &\nabla(\nabla\cdot\overline{A})-\nabla^2\overline{A}=\mu_0\epsilon_0(-\frac{\partial^2}{\partial{t^2}}\overline{A}-\frac{\partial}{\partial{t}}\nabla\phi)+\mu_0\overline{J}\\ \end{aligned}
∇ ⋅ A ‾ = − μ o ϵ 0 ∂ ∂ t ϕ \nabla\cdot\overline{A}=-\mu_o\epsilon_0\frac{\partial}{\partial{t}}\phi ,则有：
∇ 2 A ‾ − μ 0 ϵ 0 ∂ 2 ∂ t 2 A ‾ = − μ 0 J ‾ \nabla^2\overline{A}-\mu_0\epsilon_0\frac{\partial^2}{\partial{t^2}}\overline{A}=-\mu_0\overline{J}

A ‾ = z ^ μ 0 ∂ ∂ t Π \overline{A}=\hat{z}\mu_0\frac{\partial}{\partial{t}}\Pi

z ^ ( ∇ 2 μ 0 ∂ ∂ t Π − μ 0 2 ϵ 0 ∂ 3 ∂ t 3 Π ) = μ 0 J ‾ = z ^ ( − μ 0 ) ∂ ∂ t ( q l cos ⁡ ω t δ ( r ) ) ∇ 2 Π − μ 0 ϵ 0 ∂ 2 ∂ t 2 Π = − q l cos ⁡ ω t δ ( r ) \begin{aligned} \hat{z}(\nabla^2\mu_0\frac{\partial}{\partial{t}}\Pi-{\mu_0}^2\epsilon_0\frac{\partial^3}{\partial{t^3}}\Pi)&=\mu_0\overline{J}\\ &=\hat{z}(-\mu_0)\frac{\partial}{\partial{t}}(ql\cos{\omega t}\delta(r))\\ \nabla^2\Pi-\mu_0\epsilon_0\frac{\partial^2}{\partial{t^2}}\Pi&=-ql\cos{\omega t}\delta(r) \end{aligned}

∇ 2 Π = 1 r ∂ 2 ∂ r 2 ( r Π ) \nabla^2\Pi=\frac{1}{r}\frac{\partial^2}{\partial{r^2}}(r\Pi)

1 r [ ∂ 2 ∂ r 2 ( r Π ) − μ 0 ϵ 0 ∂ 2 ∂ t 2 Π ] = 0 Π = c r cos ⁡ ( k z − ω t ) \frac{1}{r}[\frac{\partial^2}{\partial{r^2}}(r\Pi)-\mu_0\epsilon_0\frac{\partial^2}{\partial{t^2}}\Pi]=0\\ \Pi=\frac{c}{r}\cos{(kz-\omega t)}

∭ Δ V → 0 d V ( ∇ 2 Π − μ 0 ϵ 0 ∂ 2 ∂ t 2 Π ) = − q l cos ⁡ ω t ∭ Δ V → 0 d V ( ∇ ⋅ ( ∇ Π ) ) = ∯ Δ S → 0 d S ‾ ⋅ ∇ Π = lim ⁡ r → 0 ∫ 0 π d θ ∫ 0 2 π r 2 sin ⁡ θ d ϕ ⋅ ∂ Π ∂ r = lim ⁡ r → 0 4 π r 2 ( − c r cos ⁡ ( k r − ω t ) − c k r sin ⁡ ( k r − ω t ) ) = − 4 π c cos ⁡ ( ω t ) \begin{aligned} \iiint_{\Delta{V}\rightarrow{0}}dV(\nabla^2\Pi-\mu_0\epsilon_0\frac{\partial^2}{\partial{t^2}}\Pi)&=-ql\cos{\omega t}\\ \iiint_{\Delta{V}\rightarrow{0}}dV(\nabla\cdot(\nabla\Pi))&=\oiint_{\Delta{S}\rightarrow{0}}d\overline{S}\cdot\nabla\Pi\\ &=\lim_{r\rightarrow0}\int_{0}^{\pi}d\theta\int_{0}^{2\pi}r^2\sin{\theta}d\phi\cdot\frac{\partial\Pi}{\partial{r}}\\ &=\lim_{r\rightarrow0}4\pi r^2(-\frac{c}{r}\cos(kr-\omega t)-\frac{ck}{r}\sin(kr-\omega t))\\ &=-4\pi c \cos(\omega t) \end{aligned}

Π = q l 4 π r cos ⁡ ( k z − ω t ) \Pi=\frac{ql}{4\pi r}\cos(kz-\omega t)

z ^ = r ^ ( z ^ ⋅ r ^ ) + θ ^ ( z ^ ⋅ θ ^ ) + ϕ ^ ( z ^ ⋅ ϕ ^ ) = r ^ cos ⁡ θ − θ ^ sin ⁡ θ A ‾ = z ^ μ 0 q l ω 4 π r sin ⁡ ( k r − ω t ) = ( r ^ cos ⁡ θ − θ ^ sin ⁡ θ ) μ 0 q l ω 4 π r sin ⁡ ( k r − ω t ) = r ^ A r + θ ^ A θ A r = − sin ⁡ θ ⋅ μ 0 ω q l 4 π r sin ⁡ ( k r − ω t ) A θ = − cos ⁡ θ ⋅ μ 0 ω q l 4 π r sin ⁡ ( k r − ω t ) H ‾ = 1 μ 0 ∇ × A ‾ = 1 μ 0 r 2 sin ⁡ θ ∣ r ^ r θ ^ r sin ⁡ θ ϕ ^ ∂ ∂ r ∂ ∂ θ ∂ ∂ ϕ A r r A θ 0 ∣ = ϕ ^ ω q l k 4 π r sin ⁡ θ [ − cos ⁡ ( k r − ω t ) + 1 k r sin ⁡ ( k r − ω t ) ] E ‾ = − ∂ A ‾ ∂ t − ∇ ϕ = k 2 q l 4 π ϵ 0 r ( r ^ 2 cos ⁡ θ ( 1 k r sin ⁡ ( k r − ω t ) + 1 k 2 r 2 cos ⁡ ( k r − ω t ) ) + θ ^ sin ⁡ θ ( 1 k r sin ⁡ ( k r − ω t ) + ( 1 k 2 r 2 − 1 ) cos ⁡ ( k r − ω t ) ) ) \begin{aligned} \hat{z}&=\hat{r}(\hat{z}\cdot\hat{r})+\hat{\theta}(\hat{z}\cdot\hat{\theta})+\hat{\phi}(\hat{z}\cdot\hat{\phi})\\ &=\hat{r}\cos\theta-\hat\theta\sin\theta\\ \overline{A}&=\hat{z}\mu_0\frac{ql\omega}{4\pi r}\sin(kr-\omega t)\\ &=(\hat{r}\cos\theta-\hat\theta\sin\theta)\mu_0\frac{ql\omega}{4\pi r}\sin(kr-\omega t)\\ &=\hat{r}A_r+\hat\theta A_{\theta}\\ A_r&=-\sin\theta\cdot\mu_0\frac{\omega ql}{4\pi r}\sin(kr-\omega t)\\ A_{\theta}&=-\cos\theta\cdot\mu_0\frac{\omega ql}{4\pi r}\sin(kr-\omega t)\\ \overline{H}&=\frac{1}{\mu_0}\nabla\times\overline{A}\\ &=\frac{1}{\mu_0r^2\sin{\theta}}\left |\begin{array}{cccc} \hat{r} &r\hat\theta & r\sin\theta\hat\phi \\ \frac{\partial}{\partial{r}} &\frac{\partial}{\partial\theta} & \frac{\partial}{\partial\phi} \\ A_r & rA_{\theta} & 0 \\ \end{array}\right|\\ &=\hat\phi\frac{\omega qlk}{4\pi r}\sin\theta[-\cos(kr-\omega t)+\frac{1}{kr}\sin(kr-\omega t)]\\ \overline{E}&=-\frac{\partial\overline{A}}{\partial{t}}-\nabla\phi\\ &=\frac{k^2ql}{4\pi\epsilon_0r}(\hat{r}2\cos\theta(\frac{1}{kr}\sin(kr-\omega t)+\frac{1}{k^2r^2}\cos(kr-\omega t))+\hat{\theta}\sin\theta(\frac{1}{kr}\sin(kr-\omega t)+(\frac{1}{k^2r^2}-1)\cos(kr-\omega t))) \end{aligned}\\

H ‾ = − ϕ ^ ω q l k 4 π r sin ⁡ θ cos ⁡ ( k r − ω t ) E ‾ = − θ ^ k 2 q l 4 π ϵ 0 r sin ⁡ θ cos ⁡ ( k r − ω t ) S ‾ = E ‾ × H ‾ = r ^ k 3 ω q 2 l 2 ( 4 π r ) 2 ϵ 0 sin ⁡ 2 θ cos ⁡ 2 ( k r − ω t ) \begin{aligned} &\overline{H}=-\hat\phi\frac{\omega qlk}{4\pi r}\sin\theta\cos(kr-\omega t)\\ &\overline{E}=-\hat\theta\frac{k^2ql}{4\pi\epsilon_0 r}\sin\theta\cos(kr-\omega t)\\ &\overline{S}=\overline{E}\times\overline{H}=\hat{r}\frac{k^3\omega q^2l^2}{{(4\pi r)}^2\epsilon_0}\sin^2\theta\cos^2(kr-\omega t) \end{aligned}

H ‾ = 0 E ‾ = q l 4 π ϵ r 3 ( r ^ 2 cos ⁡ θ + θ ^ sin ⁡ θ ) \begin{aligned} \overline{H}&=0\\ \overline{E}&=\frac{ql}{4\pi \epsilon r^3}(\hat{r}2\cos\theta+\hat\theta\sin\theta) \end{aligned}

H ‾ = ϕ ^ ω q l 4 π r 2 sin ⁡ θ sin ⁡ ( − ω t ) = ϕ ^ l 4 π r 2 sin ⁡ θ d d t ( q cos ⁡ ω t ) = θ ^ I l 4 π r 2 sin ⁡ θ \begin{aligned} \overline{H}&=\hat\phi\frac{\omega ql}{4\pi r^2}\sin\theta\sin(-\omega t)\\ &=\hat\phi\frac{l}{4\pi r^2}\sin\theta\frac{d}{dt}(q\cos\omega t)\\ &=\hat\theta\frac{Il}{4\pi r^2}\sin\theta \end{aligned}

• 0
点赞
• 1
评论
• 0
收藏
• 一键三连
• 扫一扫，分享海报

04-20 185
10-27 4570

10-31 200
11-13 2338
05-23 6139
06-10 64
12-09 7021
11-09 2836
03-27 2069
04-25 129
03-05 1798